Pemberdayaan Siswa Melalui Peningkatan Kemampuan Baca-Tulis Kitab Ta’lim Al-Muta’allim: Studi Pembelajaran Siswa Masjid Al-Ma’had Dukupuntang Kabupaten Cirebon - Theguh Saumantri (UIN Siber Syekh Nurjati Cirebon, 2022)
Education in the pandemi era has turned to online media. Learning from home or online becomes one that must be lived by students in Indonesia. This is because as an effort to prevent Covid-19. This is experienced by the students who are in the neighborhood of Al-Ma'had Mosque in Dukupuntang Cirebon Regency. Online learning activities have been running since the beginning of the pandemi. But online learning activities have a positive and negative impact. One of the negative impacts seen from students is the decrease in learning motivation due to the impact of this pandemi. Through the routine of studying the book of Ta'lim Muta'allim, it is hoped that it can foster the motivation to learn from the students, but to reveal the values contained in the book of Ta'lim Muta'alim, it is necessary to be able to read and write the yellow book that collects so that students can learn a wisdom. Research methods based on observation as a scientific way to obtain data with a specific purpose and usefulness. In this study, the results of the discussion will be conveyed that student empowerment activities through improving the ability to read and write the yellow book at the Al-ma'had Mosque become a routine activity to study students to learn the values contained in the book of Ta'lim Muta'alim and make motivation to learn during pandemi era